Synthesis and crystal structure of C2/c Ca(Co, Mg)Si2O6 pyroxenes: effect of the cation substitution on cell volume. (1st October 2017) - Gori, C.; Tribaudino, M.; Mantovani, L.; Gatta, G. D.; Delmonte, D.; Gilioli, E.; Mezzadri, F.; Calestani, G.
A series of clinopyroxenes along the CaMgSi2O6–CaCoSi2O6 join was synthesized by quenching from melts at 1500°C and subsequent annealing at 1250°C (at 0.0001 GPa). This protocol proved to be the most effective to obtain homogenous, impurity-free and stoichiometric pyroxenes. Electron microprobe analyses in energy dispersive mode were conducted and single-crystal X-ray diffraction data were collected on Ca (CoxMg1–x)Si2O6 pyroxenes with x = 0.2, 0.4, 0.5, 0.6. Effects of cation substitution at the M1 site are described. The experimental findings of this study allow us to extend the comparative analysis of the structural features of pyroxenes with divalent cations at the M1 and M2 sites.